Analysis of Elementary School Teachers' Readiness In Co-Curricular Learning In The Independent Curriculum - Sulistiyono, Ferry; Triyanto, Triyanto; Rawanoko, Endrise Septina (Universitas Sebelas Maret, 2026)
Co-curricular learning is learning that occurs alongside intra-curricular learning, aiming to achieve predetermined learning objectives and provide authentic experiences. This study aims to analyze teacher readiness for independent curricular and co-curricular learning in grades IV, V, and VI of SD Negeri 3 Kuncen, focusing on co-curricular learning planning, implementation, and assessment. This research method uses a qualitative descriptive approach. Data analysis in this study uses the Miles and Huberman model, focusing on data reduction, data display, and conclusion drawing, and the data's validity was established through source triangulation. The results of the study indicate that (1) teacher readiness in co-curricular learning planning is still low: (2) teacher readiness in implementing co-curricular learning is not optimal, 2 out of 3 teachers have only just implemented co-curricular learning: and (3) teacher readiness in implementing co-curricular learning assessment is sufficient because teachers have implemented summative assessments but formative assessments have not been carried out. This study concludes that it is necessary to develop co-curricular modules that support the independent curriculum's co-curricular learning.